Síntese, análise estrutural e aplicações de complexos de metais de transição como agentes antioxidantes. - Ceolin, Joice (2017)
In this study, fifteen complexes were synthesized from the ligands derived from the condensation of 8-hydroxy-2-quinolinecarboxaldehyde with the primary amines: 2-aminoethanol (ethanolamine), 2-amino-1,3-propanediol (serinol) and 2-amino -2- (hydroxymethyl) -1,3-propanediol (TRIS), yielding the ligands L1, L2 and L3, respectively. Three complexes were obtained with the L1 ligand: L1C1-Cu, L1C2-Ni and L1C3-Zr; L2C2-Cu, L2C3-Ni, L2C4-Ni, L2C5-Ni and L2C6-ZrL2 ligand complexes, and finally six complexes with L3 ligand: L3C1-Cu, L3C2-Cu, L3C3-Ni, L3C4-V, L3C5-Zr and L2C6-Zr. The characterization of the complexes and ligands was performed by spectroscopic and electrochemical methods, calculations of the Density Functional Theory and X-ray diffraction of monocrystals. Structural analysis showed that the ligands L2 and L3 present tautomerism, were obtained in the open (Schiff base) and cyclized (1,3-oxazolidine) forms, and the L1 ligand only in the open form. The theoretical calculations of DFT confirm this tendency of cyclization by stabilization with a lower energy. All the products obtained were tested against the photoreduction method of NBT, allowing a parallel relation to the antioxidant activity of the enzyme superoxide dismutase, thus obtaining a result of antioxidant activity in the order of 0.22 μM, considered a very promising index for further studies of in vivo activity.